Reflections of the Ethics on Coexisting with Disaster - Lo, Ed. D., H.W. Angela; Shieh, Ed.D., Vincent; Shiah, PhD, Yung-Jong (Bangladesh Journal of Bioethics, 2020)
With the increasing number of human disasters in recent years, disaster service workers are faced with an ever-growing challenge of criticism concerning their professional competence. The workers also realize the limitation inherent in their practice, as well as bioethics problems regarding autonomy and heteronomy. Therefore, professionals and researchers of human service devote to the issue of post-disaster rehabilitation of the people so as to identify an effective way and practice to aid the post-disaster individual, family and community. This study explores the effectiveness of rehabilitative function of disaster service workers through the action research of Typhoon Morakot and the 2014 Gas Explosion in Kaohsiung City, Taiwan. The case studies serves as a platform for the discussion of principles of bioethics and the analysis of the process of self-discipline of the workers of human services in hope of ultimately establishing bioethical principles for heteronomy during disasters and work indicators for post-disaster community restoration. Discuss Issues are 1. How can self-discipline in bioethics be achieved for the human service workers during times of disaster? 2. In post-disaster reconstruction, how does the human service worker take into? account bioethical principles to serve and partake in the restoration of the postdisaster life of community residents? 3. During the process of a disaster research, what are the bioethical considerations to be taken into for the test subjects? Conclusion and suggestions: To formulate indicators for a post-disaster “community of health and wellness;” to establish bioethical principles of heteronomy for disaster service workers